A critique of Bangladeshi adoption of basel type capital regulation: an institutional view - A K M Kamrul Hasan; Yasushi Suzuki (Financial Internet Quarterly, 2020)
International concern on bank capital and minimum capital adequacy was first raised in 1980, in the G-10 countries governors meeting at the Bank for International Settlements (BIS) to respond to a series of bank failures and financial instability observed in Western developed economies. Later, the Basel Committee on Banking Supervision (BCBS) of the BIS proposed the Basel accord I, II and III in 1988, 2004 and 2010, respectively. Bangladesh Bank (BB) has introduced the 'capital to risk weighted assets'-based approach for assessing the capital adequacy of banks in 1996 and later formally introduced the Basel framework in the early 2000s for its regulated banks. However, during Basel accord II and III implementation period (2009-2018), the banking industry accumulated huge non-performing loans which eroded its profitability. This creates a skepticism regarding any loopholes within the institutions. This paper argues that the näive and excess reliance on External Credit Assessment Institutions (ECAIs') credit rating in the process of adopting the Basel-type capital adequacy amounted to a risky strategy for the Bangladeshi banking industry in a sense that ECAIs allocate less efforts on accumulation of credit risk screening skills . We also document that the huge transaction cost and high coupon rate embedded within the debt instrument like the subordinated debt (sub-debt) issued by the regulated banks as Tier 2 capital might shrink the bank's profitability and its contribution to the national exchequer.
Keywords: E58; K20; K23; 330; BCBS; Basel accord; ECAIs regulation; Sub-debt regulation